THE INVESTIGATION OF END MILL FEEDS ON CNC ROUTER MACHINE USING VIBRATION METHOD - Agung Wahyudi Biantoro; Heru Maryanto; Arif Kusnan Hidayanto; Abdul Hamid (SINERGI, 2020)
Vibration on End Mill Feeds will occur due to friction between the workpiece and end mill. The friction which occurs will cause tool wear in the insert blade. At this point, the tool wear experienced by the end mill can be seen from the imperfect feed of the workpiece that is resulted. Therefore, it is necessary to find out a method that can quickly and accurately detect tool wear at the end mill. The one that was experimented in this study was the vibration method. The vibration response was measured at their x, y, and z axes with rotation speeds of 2500 rpm, 3500 rpm, and 4500 rpm. At the broken end mill, it was shown that frequencies resulted did not affect the rotation while in the standard end mill. The initial frequency was highly influenced by spindle rotations treated on it.